Epigenetic agents, zebularine and valproic acid, inhibit the growth of the oral squamous cell carcinoma cell line HSC4 in vitro and in vivo - Shuhei Takahashi (Discover Oncology, 2025)
Abstract Objectives This study explored the potential of Zebularine (Zeb), a DNA methyltransferase inhibitor (DNMTi), and Valproic acid (Vpa), a histone deacetylase inhibitor (HDACi), as a combined treatment strategy for OSCC. Materials and methods OSCC cell lines, HSC4 (well-differentiated type) and SAS (poorly differentiated type), were cultured and treated with Zeb, Vpa, and their combinations. Cell viability, mRNA expression of P16, P21, NPY, and RASSF1 using quantitative reverse transcription polymerase chain reaction (qRT-PCR), DNA methylation using methylation-specific PCR (qMSP), and in situ HDAC activity were analyzed in vitro. In vivo, a xenograft tumor formation assay was conducted using male BALB/Slc-nu nude mice, in accordance with the Basel Declaration and The ARRIVE guidelines 2.0. Tumor samples were analyzed by qRT-PCR, and qMSP. Results In vitro experiments using the HSC4 and SAS cell lines revealed significant cytotoxic effects and upregulation of tumor suppressor genes (P16, P21, NPY, and RASSF1) after treatment with Zeb + Vpa. In vivo xenograft assay in nude mice treated with Zeb + Vpa demonstrated reduced tumor volume in HSC4 cell-transplanted tumors without significant adverse effects on the body weights of the mice, whereas no significant reduction in tumor size was observed in SAS cell-transplanted tumors compared with controls. Molecular analysis confirmed elevated gene expression levels and reduced DNA methylation percentages in the treated tumors, with a more pronounced effect in HSC4 compared to SAS. Conclusions These findings suggest that the combination of Zeb and Vpa holds promise as an effective and low-toxicity therapeutic strategy for well-differentiated type of OSCC.